Application of an instructional model based on perceptual discrimination to teach concepts of materials and manufacturing processes in design courses - Santos, Ivan Mota; Botelho, Róber Dias; Oliveira, Paulo Miranda (Seven Editora, 2024)
The objective of this work is to experiment with an instructional model based on perceptual discrimination for the teaching of concepts in design. The process of developing this model was based on the understanding of how the pedagogical relationship between teachers and design students is established in the search for expertise in the area and, with that, to propose a didactic-pedagogical model capable of assisting in the processing of information, in order to enhance the training of new professionals based on an integrated educational system. This work is part of the teaching of design and, consequently, of education. Its focus is dedicated to the use of educational technology resources in pedagogical situations within bachelor's degree courses in design. The selected starting criteria contextualize its development and implementation, in parameters recently tested and presented by the science of learning and cognitive science, with main interest in the use of perceptual discrimination. It is understood that the model can enhance the teaching of design by allowing greater dynamics, flexibility and technological integration, especially in the first years of the course; The results of experiments on laypeople with no knowledge of the subject demonstrate how successful the technology has been in this aspect. The results corroborate the idea of optimizing the process and, therefore, would be able to reduce the time needed for pedagogical fulfillment in certain phases of teaching; The results of the application in an open course applied at a distance and also used with regular course design students corroborate this point. The protocol applied favors technological advancement in the search for continuous improvement of teaching in its entirety;  The modules, once built, are easy to reapply, with simple adjustments, providing the continuous evolution of the model, whether in updating content, adjusting praise and feedback, or even expanding the didactic program. DOI:https://doi.org/10.56238/sevened2024.009-024